Analysis Of Strengthening CSR Partnership Networks To Increase Income Generating PTN-BH - Azizul Kholis; Nasirwan; Silalahi, Tauada; Muhammad Yusuf (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
Income Generating for Unimed is very important to develop because Unimed as a candidate for Legal Entity State Universities in the future is required to be able to increase PNBP from various sectors. However, this CSR potential cannot yet be optimally achieved to become a source of income for Medan State University. This research aims to analyze opportunities and strengthen CSR funding partnership networks that can be implemented by universities. This research uses quantitative techniques in data analysis, namely: testing is carried out on policy determining variables in strengthening CSR partner networks. while testing the relationship between variables is calculated with the help of SmartPLS software. The research results show that support from the industrial world, partnerships and government regulations have an influence on the potential for CSR funds as income generating for universities, while support from universities has no effect on the potential for CSR funds. The government's role in regulating the management of CSR funds provides benefits for universities, especially universities in the PTN BH category.